2012
DOI: 10.1074/jbc.m112.373738
|View full text |Cite
|
Sign up to set email alerts
|

Transcription Factor NFAT1 Activates the mdm2 Oncogene Independent of p53

Abstract: Background: Mdm2 oncogene expression is regulated by p53-dependent and -independent mechanisms. Results: The NFAT1 transcription factor binds to the mdm2 P2 promoter and transactivates mdm2 independent of p53. Conclusion: NFAT1 is a transcriptional activator of the mdm2 oncogene. Significance: The identification of p53-independent control of mdm2 expression by NFAT1 will increase the understanding of the roles of NFAT1 in cancer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
80
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 52 publications
(84 citation statements)
references
References 39 publications
3
80
1
Order By: Relevance
“…Thus, we identified that HBXIP could increase the ubiquitination levels of p53 and that the effect of HBXIP on p53 was attenuated by MDM2 siRNA in the cells. Many studies have demonstrated that the levels of p53 are decreased by a variety of oncoproteins through up-regulating MDM2 in cancers (57,58). Here we found that HBXIP enhanced the degradation of p53 through up-regulating MDM2.…”
Section: Journal Of Biological Chemistrysupporting
confidence: 58%
“…Thus, we identified that HBXIP could increase the ubiquitination levels of p53 and that the effect of HBXIP on p53 was attenuated by MDM2 siRNA in the cells. Many studies have demonstrated that the levels of p53 are decreased by a variety of oncoproteins through up-regulating MDM2 in cancers (57,58). Here we found that HBXIP enhanced the degradation of p53 through up-regulating MDM2.…”
Section: Journal Of Biological Chemistrysupporting
confidence: 58%
“…In NFAT1 and NFAT4 deficient mice, immune cells are resistant to activation-induced cell death, hyperactivation and defective Fas ligand production, highlighting their tumor suppressor activities [62,63]. However, NFAT1 has been shown to induce MDM2 transcription and inactivate p53 in breast cancer cells [64]. Baumgart et al previously report that NFAT1 expression correlates with advanced stage pancreatic cancer by silencing the tumor suppressor gene p15 [65].…”
Section: Nfats In Tumorigenesis and Proliferationmentioning
confidence: 95%
“…For example, it will be interesting to determine the tissue-specific and stress-specific factors that control the expression of MDM2 from the P2 promoter. Originally identified as p53-responsive, it is now clear that other transcription factors can modulate expression from this promoter 30,31 .…”
Section: Mdm Transcriptional Regulationmentioning
confidence: 99%